Гепатопротекторные свойства квертулина при экспериментальной антихеликобактерной терапии = Kvertulin hepatoprotective properties in experimental therapy of H. Pylori - Shuhtina, Irina N (Journal of Education, Health and Sport, 2015)
Shuhtina I N. Гепатопротекторные свойства квертулина при экспериментальной антихеликобактерной терапии = Kvertulin hepatoprotective properties in experimental therapy of H. Pylori. Journal of Education, Health and Sport. 2015;5(3):47-54. ISSN 2391-8306. DOI: 10.5281/zenodo.16206 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A47-54 https://pbn.nauka.gov.pl/works/547272 http://dx.doi.org/10.5281/zenodo.16206 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015. УДК 616.33+342.092 ГЕПАТОПРОТЕКТОРНЫЕ СВОЙСТВА КВЕРТУЛИНА ПРИ ЭКСПЕРИМЕНТАЛЬНОЙ АНТИХЕЛИКОБАКТЕРНОЙ ТЕРАПИИ Kvertulin hepatoprotective properties in experimental therapy of H. pylori И. Н. Шухтина I N Shuhtina ГП «Украинский НИИ медицины транспорта» МЗ Украины GP Ukrainian Research Institute of medical transport of Ministry of health of Ukraine Abstract The Aim. Determination of hepatoprotective action in experimental drug AHBT "Kvertulin" containing quercetin, inulin and citrate kaltion. Research methods. Rats were treated for 8 days FHBT (omepra-sol 1.3 mg / kg, Amoxil 50 mg / kg of clarithromycin and 7.5 mg / kg). After sacrifice on the 12th day of the experiment was determined in liver elastase activity, alkaline phosfatazy (ALP), urease, lysozyme, catalase, and malonic dialdeguide (MDA). In blood serum, except for the above long-indicators, activity alanintransaminazy (ALT). One group of rats, semichavshey AHBT additionally performed oral gel application "Qwerty-ling" within 14 days. The Results. Increase of the liver in rats treated AHBT, levels of inflammatory markers (MDA and elastase), elevated alkaline phosphatase (indicator of cholestasis), urease (an indicator of microbial contamination), and reducing the activity of lysozyme (nonspecific immunity). The degree of dysbiosis (ratio relative activities of urease and lysozyme) withdrawn Chiva-3.7 times. Rats treated AHBT, increases in serum ALT and AP activity, indicating the development of hepatitis. Gel application "Kvertulin" reduce hepatic markers of inflammation, the degree of dysbiosis, "liver" indicators in the blood serum. Conclusion. AHBT causes the development of dysbiosis and, as a consequence of hepatitis. Kvertulin has antidisbioticheskim and hepatoprotective action. Keywords: H. pylori therapy, liver, dysbiosis, hepatitis, quercetin, inulin. Реферат Цель. Определение гепатопротекторного действия при экспериментальной АХБТ препарата «Квертулин», содержащего кверцетин, инулин и цитрат кальция. Методы исследования. Крысы получали в течение 8 дней ФХБТ (омепразол 1,3 мг/кг, амоксил 50 мг/кг и кларитромицин 7,5 мг/кг). После умерщвления на 12-й день опыта определяли в печени активность эластазы, щелочной фосфатазы (ЩФ), уреазы, лизоцима, каталазы и содержание малонового диальдегида (МДА). В сыворотке крови определяли, кроме вышеперечисленных показателей, активность аланинтрансаминазы (АЛТ). У одной группы крыс, получавшей АХБТ, дополнительно проводили оральные аппликации геля «Квертулин» в течение 14 дней. Результаты. Установлено повышение в печени крыс, получавших АХБТ, уровня маркеров воспаления (МДА и эластаза), повышение активности ЩФ (показатель холестаза), уреазы (индикатор микробного обсеменения) и снижение активности лизоцима (показатель неспецифического иммунитета). Степень дисбиоза (соотношение относительных активностей уреазы и лизоцима) увеличивается в 3,7 раза. У крыс, получавших АХБТ, в сыворотке крови возрастает активность АЛТ и ЩФ, что свидетельствует о развитии гепатита. Аппликации геля «Квертулин» снижают в печени уровень маркеров воспаления, степень дисбиоза, «печеночные» показатели в сыворотке крови. Заключение. АХБТ вызывает развитие дисбиоза и, как следствие, гепатита. Квертулин обладает антидисбиотическим и гепатопротекторным действием. Ключевые слова: антихеликобактерная терапия, печень, дисбиоз, гепатит, кверцетин, инулин.